2009
DOI: 10.1063/1.3248219
|View full text |Cite
|
Sign up to set email alerts
|

High contrast chiral nematic liquid crystal device using negative dielectric material

Abstract: A liquid crystal device is demonstrated using a short-pitch ͑260 nm͒ chiral nematic with negative dielectric anisotropy. Due to dielectric coupling, an in-plane electric field switches the liquid crystal between the standing-helix ͑field-off, "dark" state͒ and lying-helix ͑field-on, transmissive state͒ configurations. We report experimental results on the optical transmission as a function of the applied field, the response time ͑as short as 35 microseconds͒ and the contrast ratio ͑1000:1͒.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…This feature suggests that the thresholdless behavior of OXD6/OXD7*_6/4 may be due to (i) the low value of κ that resulted from its high operating temperature (∼60 °C; in comparison, the other two BPLCs were driven below room temperature) and (ii) the large pitch relative to the other two BPLCs with similar conformations (i.e., OXD7* and OXD6/OXD7*_4/6 ). The rise and fall times were less than 10 ms, similar to the reported values for BPIII phases induced by banana-shaped LCs; ,, these values are much faster than those of reported single-component BPs having temperature ranges wider than 30 K. , It has been suggested that the BPLCs in banana-shaped structures experience less steric hindrance than those in T- or U-shaped molecules, resulting in lower viscosities and faster switching times in banana-shaped BPs. ,, Furthermore, we find out that the response time values of our BPLCs (in OXD7* and OXD5B7F *) are independent of applied voltages. However, the other reported LCs with BPIII showed reduced switching time values (especially the rise time) by increasing applied voltages. , …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This feature suggests that the thresholdless behavior of OXD6/OXD7*_6/4 may be due to (i) the low value of κ that resulted from its high operating temperature (∼60 °C; in comparison, the other two BPLCs were driven below room temperature) and (ii) the large pitch relative to the other two BPLCs with similar conformations (i.e., OXD7* and OXD6/OXD7*_4/6 ). The rise and fall times were less than 10 ms, similar to the reported values for BPIII phases induced by banana-shaped LCs; ,, these values are much faster than those of reported single-component BPs having temperature ranges wider than 30 K. , It has been suggested that the BPLCs in banana-shaped structures experience less steric hindrance than those in T- or U-shaped molecules, resulting in lower viscosities and faster switching times in banana-shaped BPs. ,, Furthermore, we find out that the response time values of our BPLCs (in OXD7* and OXD5B7F *) are independent of applied voltages. However, the other reported LCs with BPIII showed reduced switching time values (especially the rise time) by increasing applied voltages. , …”
Section: Resultssupporting
confidence: 86%
“…The rise and fall times were less than 10 ms, similar to the reported values for BPIII phases induced by banana-shaped LCs; 35,37,45 these values are much faster than those of reported single-component BPs having temperature ranges wider than 30 K. 26,27 It has been suggested that the BPLCs in bananashaped structures experience less steric hindrance than those in T-or U-shaped molecules, resulting in lower viscosities and faster switching times in banana-shaped BPs. 12,67,68 Furthermore, we find out that the response time values of our BPLCs (in OXD7* and OXD5B7F*) are independent of applied voltages. However, the other reported LCs with BPIII showed reduced switching time values (especially the rise time) by increasing applied voltages.…”
Section: ■ Results and Discussionmentioning
confidence: 61%
“…Recently, chiral nematic LCs have been examined whereby the helicoidal pitch is made sufficiently small so as to reduce the transmission of light when the sample is sandwiched between crossed polarizers, and the helical axis is perpendicular to the substrate in the uniform standing helix (USH) geometry. [4][5][6][7][8][9] This can lead to significant improvements in the contrast ratio due to the very low transmission of light in the "Off" state, T off . The pitch, P, must be made as small as possible since, theoretically, in this geometry, T off can be expressed as 7…”
mentioning
confidence: 99%
“…Potential devices have been proposed using the flexoelectro-optic effect 7 or dielectrically driven out-of-plane rotation of the helical axis using negative dielectric anisotropy materials. 9 In this letter, we present results on a device that exhibits electro-optic switching with response times less than 100 ls for full intensity modulation. The device is based upon in-plane addressing of very short pitch polymer stabilized chiral nematic LCs using a commercial in-plane switching (IPS) cell architecture.…”
mentioning
confidence: 99%
“…Within the band, the circularly polarized incident light with the same handedness as the cholesteric helix is reflected while the opposite handedness is transmitted. The photonic band edges (PBEs) occur at λ s = n o p and λ l = n e p. The unique properties of this one-dimensional self-organized photonic band gap structure as distributed Bragg reflector has stimulated a wide variety of applications [1][2][3][4]. The first unambiguous demonstrations of lasing in dye-doped CLCs were carried out by Kopp and Genack et al [5].…”
Section: Introductionmentioning
confidence: 99%